2017
DOI: 10.1158/1535-7163.mct-16-0484
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of the Novel Prostamide, 15-Deoxy, Δ12,14-Prostamide J2, as a Selective Antitumor Therapeutic

Abstract: 15-deoxy, Δ-prostaglandin J-ethanolamide, also known as 15-deoxy, Δ-prostamide J (15d-PMJ) is a novel product of the metabolism of arachidonoyl ethanolamide (AEA) by COX-2. 15d-PMJ preferentially induced cell death and apoptosis in tumorigenic A431 keratinocytes and B16F10 melanoma cells compared with nontumorigenic HaCaT keratinocytes and Melan-A melanocytes. Activation of the ER stress execution proteins, PERK and CHOP10, was evaluated to determine whether this process was involved in 15d-PMJ cell death. 15d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 42 publications
(51 reference statements)
0
25
0
Order By: Relevance
“…This is the first time that these activities have been reported for this type of prostaglandins because the studies focus on anti-inflammatory activity. However, some studies have been found about cytotoxic effects of prostaglandin D (PGD), which is known as a homologous receptor of chemoattractants and especially PGD 2 -EA (prostaglandin-ethanolamide) and its catabolic product, 15-deoxy-∆ 12,14 -PGJ 2 -EA, which possess cytotoxic activity against skin cancer cells with a IC 50 of 18 µM and 20 µM respectively, concluding that these are potential therapeutic against skin cancer [14,15]. Showing in this way, that prostaglandins with hydroxyl groups and carboxylic acids have good characteristics as cytotoxic agents and that these can be potentially inhibitory against some types of cancer.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…This is the first time that these activities have been reported for this type of prostaglandins because the studies focus on anti-inflammatory activity. However, some studies have been found about cytotoxic effects of prostaglandin D (PGD), which is known as a homologous receptor of chemoattractants and especially PGD 2 -EA (prostaglandin-ethanolamide) and its catabolic product, 15-deoxy-∆ 12,14 -PGJ 2 -EA, which possess cytotoxic activity against skin cancer cells with a IC 50 of 18 µM and 20 µM respectively, concluding that these are potential therapeutic against skin cancer [14,15]. Showing in this way, that prostaglandins with hydroxyl groups and carboxylic acids have good characteristics as cytotoxic agents and that these can be potentially inhibitory against some types of cancer.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…However, proliferation rates in non-cancerous cells are typically low and as a consequence, these cells have minimal protein folding loads and ER stress levels. Hence, ER stress inducing agents cause death preferentially in cancer cells because the death threshold is more readily reached [10,13]. This selective tumor targeting often results in reduced adverse effects, a desired property for chemotherapeutic agents.…”
Section: Research Papermentioning
confidence: 99%
“…The metabolic products of AEA, prostamides-E 2 , F 2α , and -D 2 , do not bind to prostaglandin receptors, and they are metabolically stable relative to prostaglandins derived from arachidonic acid (Kozak et al, 2001 ; Matias et al, 2004 ). Recently, we demonstrated that AEA was also metabolized by COX-2 to novel J series prostamides that initiated tumor cell apoptosis (Kuc et al, 2012 ; Ladin et al, 2017 ). Because epithelial cancer cells typically overexpress COX-2, AEA was metabolized to pro-apoptotic J-series prostamides in tumor cells, but J-series prostamides were not detected in non-tumor cells which had low endogenous levels of COX-2 (Soliman et al, 2016 ).…”
Section: Non-cb1/cb2 Receptor Targetsmentioning
confidence: 99%
“…Blockade of AEA degradation with the FAAH inhibitor, URB597, increased J-series prostaglandin synthesis and apoptosis; however, inhibition of CB1, CB2, and TRPV-1 receptors using selective antagonists did not reverse this effect (Soliman and Van Dross, 2016 ). Furthermore, cell treatment with exogenous 15-deoxy, Δ 12, 14 prostamide J 2 (15d-PMJ 2 ), the most abundant J-series product of AEA metabolism by COX-2, also caused cell death in vitro and in vivo (Ladin et al, 2017 ). Reports by Pastos et al also demonstrated that COX-2 was required to induce death in cancer cells treated with AEA (Patsos et al, 2005 , 2010 ).…”
Section: Non-cb1/cb2 Receptor Targetsmentioning
confidence: 99%